Prognosis of Multifocal Papillary Thyroid Carcinoma. (30th December 2013) - Kuo, Sheng-Fong; Lin, Shu-Fu; Chao, Tzu-Chieh; Hsueh, Chuen; Lin, Kun-Ju; Lin, Jen-Der
Abstract : This study was to investigate the clinical features and therapeutic outcomes of multifocal papillary thyroid microcarcinoma (PTMC). A total of 2, 418 papillary thyroid carcinoma (PTC) patients had undergone thyroidectomy in one medical center between 1977 and 2010. There were 483 (20.0%) diagnosed with multifocal PTC. The percentage of multifocal PTC was higher in PTMC patients (22.0%) than in non-PTMC patients (19.5%). Demographic and clinical characteristics of PTMC and multifocal PTC in PTC patients were traced. Multifocal PTC patients presented with smaller tumors at an older age, and a higher percentage underwent total or complete thyroidectomy. These patients also showed a higher incidence of postoperative disease progression than did unifocal PTC patients. Comparison of 483 patients with multifocal PTMC and non-PTMC tumors showed a higher incidence of postoperative disease progression in patients with non-PTMC; otherwise, there was no statistical difference in disease-specific and total mortality between these two groups. In conclusion, the incidence of multifocal PTMC was not lower than that of non-PTMC, and postoperative therapies were necessary for both multifocal PTMC and non-PTMC patients.